International Regulation of Environmental Management in the Arctic Zone - BARBAKOV, Oleg M.; GABISHEVA, Lyudmila K.; KRETOVA, Anastasia Yu. (Journal of Environmental Management and Tourism; Vol 10 No 5 (2019): JEMT Volume X Issue 5(37) Fall 2019DO - 10.14505//jemt.v10.5(37).09, 2019)
The strengthening of global integration processes necessitates the development of cross-border regions and the intensification of cross-border cooperation in the field of environmental management, which determines the relevance of this study. This issue is particularly relevant for the Arctic region, where the start of large-scale development of natural resources, development of territories and the creation of new transport routes require the development of environmental management principles that would ensure economic development, preservation of the lifestyle of indigenous people and the preservation of biodiversity. The article examines aspects of the legal characterization and regulation of natural resources’ treatment that are jointly owned or geographically located in two or more states. It is shown that political, social, sociological and economic prerequisites impose on the principles of such cooperation. Until now, the problem of joint management and use of natural resources and products of their processing remains unresolved. It is proposed to create interstate commissions, as well as concessions, as the basis for the development of natural resources’ joint use. The leading direction in the development of the situation is interstate cooperation on the biosphere’s conservation.